Turkestan region’s oralmans: issues of settlement and adaptation (Journal of history, 2019)
The present paper has focused on issues of the Kazakh Diaspora representatives came back to their historic homeland. The main goal of the research was a problem of the choice of repatriates’ settlements here in Kazakhstan, particularly in Southern Kazakhstan. The following research methods were used to write this paper as historical-comparative, and field studies. Special attention is paid to the questions of their resettlement, strength, and tribal composition of oralmans to settle in Turkestan and its environment. This region has become a center of resettlement for the Kazakhs from Uzbekistan, Iran, Afghanistan and some small groups from Turkey. The authors highlight main reasons led to the oralmans resettlement into southern region of the republic. There were researched main stages of the oralmans migration, and its special features and also problems that oralmans faced in the country. The authors underline fraternity principles and tribal relations as foundation to create local settlements as well as social and financial support of the state to ease the adaptation to Kazakhstan.